Building Peace Through Qur’anic Interpretation in Muslim Communities in the Post-Conflict West Kalimantan - Syarif Syarif; Saifuddin Herlambang (Ulumuna, 2023)
This study explores building peace in post-conflict areas in the West Kalimantan area, Indonesia, especially among Muslim communities that had experienced ethnic conflict in 1999. This qualitative research with a phenomenological approach observes and conducts in-depth interviews with the Muslim community, both ethnic Malay Sambas and ethnic Madurese. In addition, the author also conducted interviews with several religious leaders in West Kalimantan. This study found that there are still few religious leaders who carry out conflict resolution through contextual interpretation of the Qur’an in accordance with social conditions in West Kalimantan. In principle, West Kalimantan has an opportunity to become an area of tolerance, especially in the post-ethnic conflict area of Sambas. With the characteristics of a moderate Muslim society, social interaction between ethnicities, and genealogically the Ulama in West Kalimantan conveying moderate Islamic messages, the West Kalimantan area has the potential to become a peaceful area following the conflict. However, all elements of government, education, and religious leaders must synergize with each other in building peace in West Kalimantan. The role of religious leaders in ethnic conflicts is indispensable, especially since religious leaders have charismatic authority that is easy for their followers to follow. Therefore, religious leaders must deliver messages of peace through their charismatic authority.